2022
DOI: 10.1108/ecam-01-2022-0039
|View full text |Cite
|
Sign up to set email alerts
|

Influence of social media adoption on the performance of construction small and medium-sized enterprises (SMEs) in Abuja – Nigeria

Abstract: PurposeThe purpose of this paper is to examine the influence of social media adoption on the performance of construction small and medium-sized enterprises (SMEs).Design/methodology/approachConstruction SMEs owners and managers in Nigeria were surveyed using questionnaires to gather data. Partial least square structural equation modeling (PLS-SEM) was employed to assess measurement reliability and validity, as well as the hypothesized paths provided in the conceptual model that formed part of the final conclus… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(13 citation statements)
references
References 96 publications
0
13
0
Order By: Relevance
“…(2023) and Oyewobi et al. (2022) also reported TMS as a significant factor in the adoption of technologies in organizations. Hence, the following hypothesis was created:Hypothesis Top management support positively and significantly influences AI adoption among HR professionals.…”
Section: Literature Reviewmentioning
confidence: 93%
See 1 more Smart Citation
“…(2023) and Oyewobi et al. (2022) also reported TMS as a significant factor in the adoption of technologies in organizations. Hence, the following hypothesis was created:Hypothesis Top management support positively and significantly influences AI adoption among HR professionals.…”
Section: Literature Reviewmentioning
confidence: 93%
“…This is supported by studies conducted by Duan et al (2012) and Hsu et al (2019), who reported that TMS facilitates the relationship between openness to technology adoption in organizations. Furthermore, Maroufkhani et al (2023) and Oyewobi et al (2022) also reported TMS as a significant factor in the adoption of technologies in organizations. Hence, the following hypothesis was created: Hypothesis 4.…”
Section: Top Management Support and Ai Adoptionmentioning
confidence: 96%
“…Despite extensive research on the individual and organizational impacts of SM use [35,36], its effects at the project level, particularly in the construction sector, are less understood, warranting further exploration [7]. Recent studies have begun to reveal the benefits of SM use in construction organizations, such as enhanced knowledge accessibility, reduced costs, and improved customer relations [37]. Facebook, LinkedIn, and Twitter have been identified as popular SM platforms among construction professionals [20], while in China, platforms like WeChat and DingTalk are gaining prominence in various industries, including construction [23].…”
Section: Using Sm In Project Teamsmentioning
confidence: 99%
“…Recent studies have shown that the social network model in construction fosters professional trust and strong communication, leading to high-performance teams [103]. SM's positive impact on project management includes time reduction [104] and their significant role in improving small and medium-sized enterprises' business performance by increasing knowledge accessibility and reducing costs [37].…”
Section: Sm and Team Performancementioning
confidence: 99%
“…The prevalence of social media has sparked considerable interest among scholars and business practitioners, as evidenced by the extensive research conducted by Mazurek et al (2018), Al Halbusi et al (2022), Oyewobi et al (2022), and Kanwar and Huang (2022). Since the birth of social media, the business landscape has been different.…”
Section: Introductionmentioning
confidence: 99%